Wind-induced plant motion immediately increases cytosolic calcium. - Knight, M R (1992)
Wind is one of the most unusual and more dramatic of the environmental signals to modify plant development. Wind-stimulated crops are also known to experience considerable reductions in growth and subsequent yield. There is at present no experimental data to suggest how wind signals are perceived and transduced by plant cells. We have genetically transformed Nicotiana plumbaginifolia to express aequorin and thus produced luminous plants that directly report cytosolic calcium by emitting blue light. With these plants we have found wind stimulation to cause immediate increases in cytosolic calcium and our evidence, based on the use of specific inhibitors, suggests that this calcium is mobilized from organelle sources. Our data further suggest that wind-induced movement of tissues, by mechanically stimulating and stressing constituent plant cells, is responsible for the immediate elevation of cytosolic calcium; increases occur only when the plant tissue is actually in motion. Repeated wind stimulation renders the cells refractory to further calcium signaling but responsiveness is rapidly recovered when stimulation is subsequently diminished. Our data suggest that mechanoperception in plant cells may possibly be transduced through intracellular calcium. Since mechanoperception and transduction are considered crucial to plant morphogenesis, our observations suggest that calcium could be central in the control and generation of plant form.